2018
DOI: 10.1021/acs.jafc.8b03492
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Implication of the Sorption of Perfluorooctanoic Acid by Varying Soil Size Fractions

Abstract: Sorption of perfluorooctanoic acid (PFOA), a toxic and persistent organic pollutant, by various size fractions of an agricultural soil at environmentally relevant concentrations was evaluated. PFOA sorption to all fractions involved both film diffusion and intraparticle diffusion with the rate-limiting step by the latter. PFOA isotherm data fitted a linear model. Organic matter (OM), cation exchange capacity, pore volume, and the Brunauer−Emmett−Teller area played key roles in PFOA sorption. The sorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Mesoporous hafnium oxide, a group IV transition metal oxide, is an attractive PFOA adsorption candidate. Mesoporous materials lead to increased PFOA adsorption as the diameter of PFOA is about 2 nm ( Xiang et al., 2018 ), and previous work has shown that microporous materials (<2 nm) are not ideal for PFOA adsorption ( Son et al., 2020 ). The high thermal (700°C) and chemical stability (active sites on the surface) of MHO ceramic, results from its highly coordinated hafnium.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous hafnium oxide, a group IV transition metal oxide, is an attractive PFOA adsorption candidate. Mesoporous materials lead to increased PFOA adsorption as the diameter of PFOA is about 2 nm ( Xiang et al., 2018 ), and previous work has shown that microporous materials (<2 nm) are not ideal for PFOA adsorption ( Son et al., 2020 ). The high thermal (700°C) and chemical stability (active sites on the surface) of MHO ceramic, results from its highly coordinated hafnium.…”
Section: Introductionmentioning
confidence: 99%
“…This result also suggested the affinity of BIT sorption to soils #4 and #5 in the tested concentration range was relatively constant, similar results were found for perfluorooctanoic acid sorption isotherms to all soil fractions. 51 …”
Section: Resultsmentioning
confidence: 99%
“…This result also suggested the affinity of BIT sorption to soils #4 and #5 in the tested concentration range was relatively constant, similar results were found for per-uorooctanoic acid sorption isotherms to all soil fractions. 51 The K f values-Freundlich sorption distribution coefficients-illustrate the sorption affinity between BIT and tested soils. The K f values of BIT sorption to tested soils varied between 1.83-8.60 (Table 4).…”
Section: Sorption Isothermsmentioning
confidence: 99%
“…Therefore, there are no direct evidence accounting for the high correlation between the K d values and CEC. Instead, two studies have reported that the CEC values were better-correlated with OM contents (R 2 = 0.58-0.99) (Khan et al, 2009b;Yang et al, 2020a), because CEC is mainly originated from negatively charged groups of OM (Xiang et al, 2018). Therefore, the relatively high correlation between the sorption magnitudes of the sex hormones and CEC is attributable to the relatively high correlation between CEC and OM.…”
Section: Effects Of Cation Exchange Capacity Surface Area and Particle Size Distributionmentioning
confidence: 97%